13-(2-Methylbenzyl) Berberine Is a More Potent Inhibitor of MexXY-Dependent Aminoglycoside Resistance than Berberine - Kenta Kotani; Mio Matsumura; Yuji Morita; Junko Tomida; Ryo Kutsuna; Kunihiko Nishino; Shuji Yasuike; Yoshiaki Kawamura (MDPI AG, 2019)
We previously showed that berberine attenuates MexXY efflux-dependent aminoglycoside resistance in Pseudomonas aeruginosa. Here, we aimed to synthesize berberine derivatives with higher MexXY inhibitory activities. We synthesized 11 berberine derivatives, of which 13-(2-methylbenzyl) berberine (13-o-MBB) but not its regiomers showed the most promising MexXY inhibitory activity. 13-o-MBB reduced the minimum inhibitory concentrations (MICs) of various aminoglycosides 4- to 128 fold for a highly multidrug resistant P. aeruginosa strain. Moreover, 13-o-MBB significantly reduced the MICs of gentamicin and amikacin in Achromobacter xylosoxidans and Burkholderia cepacia. The fractional inhibitory concentration indices indicated that 13-o-MBB acted synergistically with aminoglycosides in only MexXY-positive P. aeruginosa strains. Time-kill curves showed that 13-o-MBB or higher concentrations of berberine increased the bactericidal activity of gentamicin by inhibiting MexXY in P. aeruginosa. Our findings indicate that 13-o-MBB inhibits MexXY-dependent aminoglycoside drug resistance more strongly than berberine and that 13-o-MBB is a useful inhibitor of aminoglycoside drug resistance due to MexXY.